Inclusive built environment for Malaysian heritage masjid - Abd Samad, Nur Amirah; Tukiman, Izawati; Abdul Rahim, Asiah; Omar, Samini (Abdullatif Al Fozan Award for Mosque Architecture and Institut Terjemahan & Buku Malaysia Berhad, 2019)
MANY studies stress on the vulnerability of inaccessible environment to the disabled people which highlights the importance of user-friendly or barrier-free environment in today’s world (Nur Amirah, A.S. et al., 2018; Asiah, A.R. et al., 2015). With the enforcement of Persons with Disabilities Act 2008, government wishes to provide PwDs with better public transport facility, amenities and services, better health, education, information and technology, habilitation and rehabilitation, employment opportunities, as well as improved access to sports, leisure, and cultural life activities (The Star, 2010).